Ru'yah Usuliyyah li Mas'alah Istithmar Amwal al-Zakah - Bensaid, Benaouda; Rachid, Aouidad (Jurnal Fiqh, 2013)
The question of investment of zakat continues to constitute a controversial issue within the current development and application of Islamic finance. In this paper, zakat investment is discussed and analysed in light of juristic textual evidences and in view of the principles inherent within Maqasid al-Shari?ah that seek to ensure harmony with and adherence to the fundamental intents and objectives set by the lawgiver. This research utilises the inductive method in the discussion of legal reasoning deriving from Muslim sources of the law, alongside the effective contrast and comparison of legal opinions in light of the spirit of public interest (maslaha). The research endeavours to establish new inroads into contemporary fields of academic research revolving around new paradigms of understanding and undertakings of Islamic finance, while seeking the holistic and comprehensive rejuvenation of the zakat institution within contemporary societies deriving from the view of comprehensive sustainable development.